Cell‐block as ancillary tool for the diagnosis of cystic and cyst‐like jaw lesions. Issue 8 (29th February 2020) - Melo, Gilberto; Mello, Fernanda Weber; Mesquita, Ricardo Alves; Grando, Liliane Janete; Rivero, Elena Riet Correa
Abstract: Background: The cell‐block technique is a cytological diagnostic method that decreases cellular dispersion; however, its usefulness regarding intraosseous lesions is underexplored. Therefore, this study aimed to assess the diagnostic usefulness of cell‐block for cystic and cyst‐like jaw lesions. Methods: Individuals with cystic or cyst‐like jaw lesions who underwent aspiration biopsy were considered eligible. Aspiration of luminal content was prepared and processed by the cell‐block technique. Cytological evaluations were blindly performed by two trained PhD students (in a single evaluation) and one oral and maxillofacial pathologist (OMP). Cohen's kappa statistic was used to measure inter‐rater agreement. Results: The sample was composed of 52 lesions, represented by 25 radicular cysts (RC), 17 odontogenic keratocysts (OKC), 5 idiopathic bone cavities (IBC), and 5 unicystic ameloblastomas (UA). The kappa coefficient of cell‐block compared to histopathological diagnosis was 0.390 (95% confidence interval [95%CI], 0.195‐0.585) for PhD students and 0.612 (95%CI, 0.433‐0.791) for the OMP. The highest concordance rates between cell‐block and histopathological diagnosis were observed for RC (PhD = 76.0%; OMP = 80.0%) and OKC (PhD = 58.8%; OMP = 76.5%). Conflicting results were found regarding IBC (PhD = 40.0%; OMP = 80.0%) and UA, that presented the overall lowest concordance rates (PhD = 20.0%; OMP = 40.0%). Conclusion: The cell‐block technique presented a high diagnostic usefulness for detecting RC and OKC and, if associated with clinical and radiographic characteristics, might be sufficient for final diagnosis of these diseases. Regarding IBC and UA, an analysis with a higher number of cases is recommended to determine the true usefulness of the cell‐block as ancillary tool for the diagnosis of these lesions.